2019
DOI: 10.3390/molecules24173048
|View full text |Cite
|
Sign up to set email alerts
|

Pd Nanocatalyst Adorned on Magnetic Chitosan@N-Heterocyclic Carbene: Eco-Compatible Suzuki Cross-Coupling Reaction

Abstract: A novel magnetic-functionalized-multi-walled carbon nanotubes@chitosan N-heterocyclic carbene-palladium (M-f-MWCNTs@chitosan-NHC-Pd) nanocatalyst is developed in two steps. The first step entails the fabrication of a three-component cross-linking of chitosan utilizing the Debus–Radziszewski imidazole approach. The second step comprised the covalent grafting of prepared cross-linked chitosan to the outer walls of magnetically functionalized MWCNTs (M-f-MWCNTs) followed by introducing PdCl2 to generate the m-f-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For example, in recent years, different types of nanoparticle support materials were investigated; for example, metal oxides [ 29 , 30 , 31 ], zeolites [ 32 , 33 , 34 ], carbons [ 35 , 36 , 37 ], ordered porous materials [ 38 , 39 ] and synthesized polymers [ 40 ] (e.g., ionic polymers [ 41 ]) and modified natural polymers [ 42 , 43 ]. There are several studies on mixed composition for palladium nanoparticle (PdNP) support [ 44 , 45 , 46 , 47 ], and the need for a rational design of catalyst support has been emphasized [ 48 , 49 ]. In pursuit of a rational approach to the creation of a catalytic system based on PdNPs, we have chosen phosphonium salts with a sterically hindered cation with a variable fourth alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in recent years, different types of nanoparticle support materials were investigated; for example, metal oxides [ 29 , 30 , 31 ], zeolites [ 32 , 33 , 34 ], carbons [ 35 , 36 , 37 ], ordered porous materials [ 38 , 39 ] and synthesized polymers [ 40 ] (e.g., ionic polymers [ 41 ]) and modified natural polymers [ 42 , 43 ]. There are several studies on mixed composition for palladium nanoparticle (PdNP) support [ 44 , 45 , 46 , 47 ], and the need for a rational design of catalyst support has been emphasized [ 48 , 49 ]. In pursuit of a rational approach to the creation of a catalytic system based on PdNPs, we have chosen phosphonium salts with a sterically hindered cation with a variable fourth alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, chloro‐based substrate gave very low conversion (Entry 3) due to the strong C–Cl bond. [ 11 ] In both the catalysts, catalytic studies showed iodo‐ and bromo‐based aryl substrates with an electron‐withdrawing group (Entries 1, 2, 6, and 7) and showed a higher percentage of conversion than the strong electron‐donating group substituted aryl halides (Entry 4). Similarly, Entry 5 also displayed relatively high reactivity due to the weak electron‐donating ability of the CH 3 group.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7–9 ] Furthermore, owing to its strong σ donating and weak accepting ability than the commercial phosphine ligands, it enhances the crucial steps of coupling reactions such as oxidation addition and reductive elimination, which, in turn, increases the efficiency of such catalysts towards cross‐coupling reactions. [ 10,11 ] After the first report on water‐soluble NHC–Pd complex, NHC has been subsequently modified to attain homogeneous catalysts for cross‐coupling reactions. [ 12–14 ] Despite showing high reactivity, they required either high temperature, a mixture of organic solvent/additives, and in some cases, the catalyst lacked easy recoverability and recyclability, which leads to the metal contamination in the product.…”
Section: Introductionmentioning
confidence: 99%
“…The Suzuki-Miyaura cross-coupling reaction plays a signicant industrial-scale role in the production of biaryl compounds, which are widely used for a variety of industrial applications, such as the synthesis of natural products, herbicides, pharmaceuticals, polymers, and agrochemicals. [1][2][3] In general, the easy availability of the starting materials (organic halides and boronic acids), high reactivity under mild reaction conditions, the tolerance to a wide range of functionalities, the formation of nontoxic products, the small amount of catalyst used in the reaction, and the possibility of using water as a solvent or co-solvent contribute to their increasing interest. 4 Homogeneous palladium (Pd) complexes have been widely explored as catalysts for this kind of reaction.…”
Section: Introductionmentioning
confidence: 99%